2020
DOI: 10.1371/journal.pone.0230743
|View full text |Cite
|
Sign up to set email alerts
|

Pre-adult aggression and its long-term behavioural consequences in crickets

Abstract: Social experience, particularly aggression, is considered a major determinant of consistent inter-individual behavioural differences between animals of the same species and sex. We investigated the influence of pre-adult aggressive experience on future behaviour in male, last instar nymphs of the cricket Gryllus bimaculatus. We found that aggressive interactions between male nymphs are far less fierce than for adults in terms of duration and escalation. This appears to reflect immaturity of the sensory apparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…In response to the single touch stimulus, crickets tended to turn either towards it (positive turners) or away (negative turners). We never observed the aggressive mandible threat after the brief, single stimulus, which often occurs in response to repetitive stimulation 33 , 48 . However, positive turners ( n = 40 observed) occasionally lunged forward ( n = 9), exhibited body jerks ( n = 11) or generated the rival song ( n = 4), which was never shown by negative turners.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…In response to the single touch stimulus, crickets tended to turn either towards it (positive turners) or away (negative turners). We never observed the aggressive mandible threat after the brief, single stimulus, which often occurs in response to repetitive stimulation 33 , 48 . However, positive turners ( n = 40 observed) occasionally lunged forward ( n = 9), exhibited body jerks ( n = 11) or generated the rival song ( n = 4), which was never shown by negative turners.…”
Section: Resultsmentioning
confidence: 79%
“…As for LTI w/ , they were taken from the colony on the day of the moult to the last nymphal stage and kept individually in social isolation until adult maturity. These animals thus only had contact to nymphs during development, which do not interact aggressively to generate winners and losers with long-term consequences for their subsequent behaviour 33 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of studies on invertebrates showed that aggressive behavior is modulated by genetic factors (Dierick and Greenspan, 2006 ), environmental conditions (Rittschof and Robinson, 2013 ; Rillich et al, 2019 ), social influences (Kilgour et al, 2019 ; Balsam and Stevenson, 2020 ), sex (Benelli et al, 2015 ), and previous experiences (Goubault and Decuigniere, 2012 ; Rose et al, 2017 ). Indeed, previous victory and defeat induce behavioral plasticity in the form of winner and loser effects (previous victory/defeat increase the probability of winning/losing subsequent fight) (Hsu et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%